Anxiety on Primigravid Women Attending Antenatal Care Out Patient Department - Pokharel, Swechchha; Karki, Anish; Karki, Jashmita; Bhattarai, Smita; Chaudhary, Manisha; Chaudhary, Asmita (Journal of Nobel Medical College, 2026)
Background: Pregnancy is a transitory period in a woman’s life event characterized by physiological, cognitive, emotional, and social changes. So, it is natural that pregnant women are often concerned about the future. Moreover, the study aims to assess the prevalence of anxiety on primigravid women attending antenatal care Out Patient department and its association with selected demographic variables. Materials and Methods: A cross-sectional study was conducted at the antenatal care outpatient department of Nobel medical college teaching hospital, Biratnagar from March 2025 to November 2025. A total of 252 primigravid women were selected through convenience sampling. Data were collected via face-to-face interview using Pregnancy-Related Anxiety Questionnaires Revised 2. For descriptive statistic (mean, standard deviation) and for inferential statistic (Chi-square) were used for analysis. Results: Majority (79.4%) of the participants were of age less than or equal to 25 years. Majority (83.7%) of the participants were in a gestational period of 24 weeks or more. Majorities (72.6%) of the participants were in low risk of developing anxiety and there was no any association of anxiety with its socio-demographic variables. Conclusion: The finding showed that a majority of participants were at low risk of developing anxiety during pregnancy. There was no any association of anxiety with its socio-demographic variables like age, and wife education (husband and wife), occupation (husband and wife), intension of pregnancy, family support, monthly income.